2007
DOI: 10.1002/yea.1498
|View full text |Cite
|
Sign up to set email alerts
|

Can the different heat shock response thresholds found in fermenting and respiring yeast cells be attributed to their differential redox states?

Abstract: In this study we used a heat-shock (HS) reporter gene to demonstrate that respiring cells are intrinsically less sensitive (by 5 • C) than their fermenting counterparts to a sublethal heat shock. We also used an oxidant-sensitive fluorescent probe to demonstrate that this correlates with lower levels of sublethal reactive oxygen species (ROS) accumulation in heat-stressed respiring cells. Moreover, this relationship between HS induction of the reporter gene and ROS accumulation extends to respiring cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
3
4
0
Order By: Relevance
“…In conclusion, the differential effects of H 2 O 2 and ascorbate on the aerobic thermosensitivity and intrinsic thermotolerance of yeast cells grown under different conditions reflect differences in the ever‐changing physiological dynamic and redox status of these cells. This study also reinforces our earlier work implicating the cellular redox potential as playing a key role in cellular thermosensitivity (Moraitis and Curran, 2004, 2007). Further investigations will reveal to what extent each of these factors contributes to such differential effects.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In conclusion, the differential effects of H 2 O 2 and ascorbate on the aerobic thermosensitivity and intrinsic thermotolerance of yeast cells grown under different conditions reflect differences in the ever‐changing physiological dynamic and redox status of these cells. This study also reinforces our earlier work implicating the cellular redox potential as playing a key role in cellular thermosensitivity (Moraitis and Curran, 2004, 2007). Further investigations will reveal to what extent each of these factors contributes to such differential effects.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with a number of independent observations, we have previously shown that in aerobically‐grown yeast cells, the HSR is sensitized in the presence of H 2 O 2 and desensitized in the presence of ascorbate (Moraitis and Curran, 2004, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recently, we found that Mpr1 protects yeast cells by reducing the intracellular reactive oxygen species (ROS) levels under oxidative stress conditions, such as H 2 O 2 , heat shock, freeze–thaw or ethanol treatment (Nomura & Takagi, 2004; Du & Takagi, 2005, 2007). Exposure to a high temperature also produces ROS in the mitochondria, which cause oxidative stress in yeast cells (Davidson et al , 1996; Moraitis & Curran, 2004, 2007). We also isolated two Mpr1 variants with improved enzymatic functions (K63R and F65L) (Iinoya et al , 2009).…”
Section: Introductionmentioning
confidence: 99%